Improvement of the efficiency and quality in developing a new CHO host cell line. (26th June 2021) - Huhn, Steven C.; Ou, Yang; Tang, Xiaoyan; Jiang, Bo; Liu, Ren; Lin, Henry; Du, Zhimei
Abstract: Chinese hamster ovary (CHO) cells are a ubiquitous tool for industrial therapeutic recombinant protein production. However, consistently generating high‐producing clones remains a major challenge during the cell line development process. The glutamine synthetase (GS) and dihydrofolate reductase (DHFR) selection systems are commonly used CHO expression platforms based on controlling the balance of expression between the transgenic and endogenous GS or DHFR genes. Since the expression of the endogenous selection gene in CHO hosts can interfere with selection, generating a corresponding null CHO cell line is required to improve selection stringency, productivity, and stability. However, the efficiency of generating bi‐allelic genetic knockouts using conventional protocols is very low (<5%). This significantly affects clone screening efficiency and reduces the chance of identifying robust knockout host cell lines. In this study, we use the GS expression system as an example to improve the genome editing process with zinc finger nucleases (ZFNs), resulting in improved GS‐knockout efficiency of up to 46.8%. Furthermore, we demonstrate a process capable of enriching knockout CHO hosts with robust bioprocess traits. This integrated host development process yields a larger number of GS‐knockout hosts with desired growth and recombinant protein expression characteristics.